Community participation, equity and integrity in polycentric governance for climate resilience: evidence from Kenya and Zambia - van Koppen, Barbara; Amarnath, Giriraj; Mweemba, C.; Schreiner, B.; Njoroge, D.; Keega, M.; Osoro, G. (International Water Management Institute, 2023)
Inclusive community participation in bottom-up polycentric governance is at the heart of recognitional, procedural, distributional and inter-generational equity and of integrity of international, national and district-scale interventions to improve climate resilience in marginalized rural areas. This Technical Brief summarizes evidence of four ClimBeR and ACTION initiatives in Kenya, in collaboration with the Water Integrity Network, and in Zambia that operationalized these concepts into a concrete diagnosis of local water tenure as basis for the identification of solutions and their funding and implementation. At the interface between communities and government or other external support agencies, this step-wise process of co-design and implementation mobilized communities’ assets and agency of their horizontal, age-old and yet dynamic, integrated water, land and other resource governance. Typical siloes in formal vertical governance were overcome. Such community participation is probably the single most important condition for effective and sustainable performance.